Numerical Investigations on Fluid Flow and Solidification behavior during impact of a Hollow Molten Droplet on a Solid Substrate - Rout, Ronit; Patel, Virendra (International Journal of Engineering and Technology, 2018)
In thermal spraying coating process, powder materials are melted and driven towards the substrateâ€™s surface. This process involves impact of droplet and its solidification. It has been observed that central counter jet present in the hollow droplet impact on substrate. This counter jet affects total solidification time of splat and spreading pattern. The main objective of the present work is to develop a CFD model. That is able to investigate the effect of surface roughness on spreading and solidification pattern. In this work a molten ZrO2 hollow droplet impacting on a substrate of Stainless steel is investigated. The governing equations for fluid flow are solved numerically using a pressure-based finite volume method, following the SIMPLE algorithm presented by Patankar (1980). To track droplet THINC/WLIC method is used which is a VOF (Volume of Fluid) type method. To model surface tension force, the CSF (continuum surface flow) model is used. Enthalpy-based formulation is used to solve energy equation.Â